INTERNATIONAL EXPERIENCE: THE CURRENT STATE OF THE GREEN TAX SYSTEM IN CHINA AND DEVELOPMENT PROSPECTS - M. Adilov; A. Kenjabaev; A. Abdurakhmanov (Modern American Journals, 2025)
Green Taxes in many countries it is located in a period of active transformation, which is associated with the growing scale of infrastructure and social projects, as well as the need to increase natural resources. The article provides an in-depth analysis of China's experience. A scientific analysis was conducted The state of the green tax system in China and its development prospects.